Knowledge, Attitude, and Practice using the Kangaroo Method Care in Maternal with Low Birth Weight Babies - Mustikawati, Intan Silviana; Pratomo, Hadi; Martha, Evi; Murty, Ade Iva (KEMAS: Jurnal Kesehatan Masyarakat, 2022)
Newborn mortality is still quite high in the world, including Indonesia, one of which is caused by complications of premature birth. Kangaroo Method Care (KMC) is one way to keep the newborn’s body temperature warm by making direct contact between the baby’s skin and the mother’s skin. The purpose of this study was to analyze the relationship between knowledge, attitude, and practice of Kangaroo Care Method for mothers with low birth weight (LBW) infants. This study is a quantitative study with a cross-sectional approach. Respondents in this study were mothers who had LBW after treatment from the Regional General Hospital (RSUD) Koja, North Jakarta who were domiciled in Koja, Tanjung Priok, and Cilincing Districts, North Jakarta, amounting to 50 people. Data was collected using questionnaires and observations, and analyzed using the Spearman Correlation statistical test. Based on the results of the study, the average score of mother’s knowledge about Kangaroo Care Method was 21.76 (SD 1.06); the average score of the mother’s attitude towards the Kangaroo Care Method is 26.74 (SD 0.80); and the average duration of practice for Kangaroo Care Method is 2.92 hours/day (SD 0.90). Based on the results of observations, it was found that most of the LBW mothers had practiced Kangaroo Method Care by holding the right position from Kangaroo Method Care. Based on the Spearman Correlation statistical test, it was found that there was a relationship between knowledge, attitude, and practice of the Kangaroo Care Method in LBW mothers.